Learning, speech and thought in the mentally retarded - Clarke, A. D. B. (Alan Douglas Benson); Lewis, M. M. (Morris Michael) (Institute for Research into Mental Retardation. Symposia, 4 and 5, 1972)
Learning, Speech and Thought in the Mentally Retarded contains the proceedings of Symposia 4 and 5 held at the Middlesex Hospital Medical School in London on October 31, 1969 and March 20, 1970, respectively, under the auspices of the Institute for Research into Mental Retardation. This monograph presents topical problems in mental retardation, with emphasis on learning processes, speech, and thought. The application of operant learning techniques to the development of language in the retarded is highlighted. This book is comprised of four chapters and begins by outlining directions in resea.